The Watershed Leader as a Catalyst for Change. (2nd September 2019) - Bonnell, Joseph E.; Hettinger, Dallas Z.; Baird, Anne M.
Abstract: This paper describes a research project that collected information about the leadership characteristics of successful watershed coordinators in Ohio. We interviewed a total of twenty watershed coordinators who had successfully completed nonpoint source (NPS) management projects and asked them to discuss their perceptions of what made them and others like them successful. We organized the attributes identified into three themes (social, technical and administrative). Of these, social attributes like strong communication skills were considered to be the most critical for getting NPS projects completed, though technical and administrative attributes were also important. We discuss how these findings might be applied in evaluating and training watershed coordinators, and consider possible avenues for further research.